2020
DOI: 10.1016/j.jid.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Advances in Vascular Malformations

Abstract: Vascular malformations are subdivided into capillary, lymphatic, venous, arteriovenous, and mixed malformations, according to the type of affected vessels. Until a few years ago, treatment options were limited to sclerotherapy and/or surgery. Since, it has been demonstrated that the majority of vascular malformations are caused by inherited or somatic mutations in various genes. These mutations lead to hyperactivity of two major signaling pathways: the RAS/ mitogen-activated protein kinase and the phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 67 publications
(104 reference statements)
0
36
0
Order By: Relevance
“…7,31 The proliferative effect of PIK3CA mutations in PROS syndromes exhibits an apparent skewing in the pattern of affected tissues, with mesoderm-derived tissues (including vasculature and adipose tissue) being markedly affected. 32 Importantly, mosaic activating mutations in PIK3CA are also known to cause the majority of isolated lymphatic malformations (>90%) as well as a significant proportion of isolated venous malformations (25%-30%) in the nonsyndromic population 5,6,25 ; unrestrained activation of p110α in endothelial cells leads to a hyperproliferative phenotype and formation of vascular developmental tumors responsive to therapeutic PI3K inhibition. 25 Intermediate PROS phenotypes, characterized by capillary malformations with overgrowth and lipomatous neoformations, are often caused by PIK3CA mutations with intermediate oncogenic potency, including the p.E545A mutation that was detected in our study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7,31 The proliferative effect of PIK3CA mutations in PROS syndromes exhibits an apparent skewing in the pattern of affected tissues, with mesoderm-derived tissues (including vasculature and adipose tissue) being markedly affected. 32 Importantly, mosaic activating mutations in PIK3CA are also known to cause the majority of isolated lymphatic malformations (>90%) as well as a significant proportion of isolated venous malformations (25%-30%) in the nonsyndromic population 5,6,25 ; unrestrained activation of p110α in endothelial cells leads to a hyperproliferative phenotype and formation of vascular developmental tumors responsive to therapeutic PI3K inhibition. 25 Intermediate PROS phenotypes, characterized by capillary malformations with overgrowth and lipomatous neoformations, are often caused by PIK3CA mutations with intermediate oncogenic potency, including the p.E545A mutation that was detected in our study.…”
Section: Resultsmentioning
confidence: 99%
“…32 Importantly, mosaic activating mutations in PIK3CA are also known to cause the majority of isolated lymphatic malformations (>90%) as well as a significant proportion of isolated venous malformations (25%-30%) in the nonsyndromic population 5,6,25 ; unrestrained activation of p110α in endothelial cells leads to a hyperproliferative phenotype and formation of vascular developmental tumors responsive to therapeutic PI3K inhibition. 25 Intermediate PROS phenotypes, characterized by capillary malformations with overgrowth and lipomatous neoformations, are often caused by PIK3CA mutations with intermediate oncogenic potency, including the p.E545A mutation that was detected in our study. 31,32 Rare instances of familial angiolipomatosis have been reported, apparently following an autosomal dominant mode of inheritance 9 ;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research in the genetic and pathophysiologic origin of VMs demonstrated that VMs caused by abnormal signaling within vascular endothelial cells. [4] The phosphatidylinositol 3-kinase(PI3K)-protein kinase B(AKT)-mammalian target of rapamycin (mTOR) pathway plays a key role in the pathogenesis of VMs. [5] The PI3K/AKT/mTOR pathway is implicated in many cellular processes, such as cell-cycle regulation, proliferation, protein synthesis, and cell survival.…”
Section: Introductionmentioning
confidence: 99%